Case Report: Conservative management of hemophagocytic lymphohistiocytosis with fulminant hepatic failure in a pediatric leukemia patient - Paixão, Filipa; Salvada, André; Santos, Susana; Amorim, Catarina; Escobar, Carlos (Frontiers in Pediatrics, 2025)
IntroductionHemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome that can lead to multiorgan failure, including acute liver failure. While varicella infection in leukemia patients in remission is not uncommon, HLH complicated by fulminant hepatic failure is exceedingly rare.Case reportWe report the case of an adolescent with acute T-cell lymphoblastic leukemia in remission who developed varicella infection, followed by decompensated shock and acute liver failure (ALF). The patient met HLH-2004 diagnostic criteria, including fever, pancytopenia, hypertriglyceridemia, hyperferritinemia, elevated soluble interleukin-2 receptor, and bone marrow hemophagocytosis. The patient received immunosuppressive therapy according to the HLH-2004 protocol, along with antiviral therapy and supportive care, and achieved full recovery without liver transplantation. To our knowledge, this is among the few reported cases of HLH-associated acute liver failure in a pediatric leukemia patient successfully managed conservatively.DiscussionThis case highlights the diagnostic challenges of HLH in immunocompromised children, where early signs such as fever and cytopenias may be misattributed to sepsis or chemotherapy-related complications. It underscores the importance of including HLH in the differential diagnosis of ALF in high-risk patients and demonstrates that prompt recognition and targeted treatment of the hyperinflammatory state can be lifesaving, even in severe presentations.